Biochemical polymorphisms in the Malaysian water buffaloes - Tan, S. K.; Tan, Soon Guan; Jainudeen, Mohamed Razeen; Gan, Yik Yuen (Universiti Pertanian Malaysia, 1980)
Ten enzymes and proteins: transferrin, amylase, haemoglobin, esterase D, red cell acid pho.phatau, superoxide dismutase, phosphoglycolate phosphatase, glucose-6-phosphate dehydrogenase, 6-phosphogluconate dehydrogenase and soluble glutamate oxaloace.tate transaminase, from the serum and red blood cell of 88 water buffaloes, Bubalus bubahs, have been investigated by starch gel or polyacrylamide gel electrophoresis. Four of these: transferrin, amylase, haemoglobin and esterase D show electrophoretic variation at polymorphic proportions.